2003
DOI: 10.1364/ao.42.006630
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Wave Singly Resonant Optical Parametric Oscillator Placed Inside a Ring Laser

Abstract: A cw singly resonant optical parametric oscillator (SRO) was built and placed inside the cavity of a ring laser. The system consists of a diode-end-pumped Nd:YVO4 ring laser with intracavity periodically poled lithium niobate as the nonlinear gain medium of the SRO. When the laser was operated in a unidirectional mode, we obtained more than 520 mW of signal power in one beam. When the laser was operated in a bidirectional mode, we obtained 600 mW of signal power (300 mW in two separate beams). The power and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It's important to produce compact and high quality (high-efficiency and widely-tunable) MIR laser. A number of mid-infrared continuous waves based on IC-OPO have been reported [6][7][8][9][10][11][12]: Carleton et al reported a CW IC-OPO based on PPRbTiOAsO4 pumped by 1064nm Nd:YVO4 laser. At 3 W of input diode-laser, the maximum power of 65 mW of idler at 3.52 μm was obtained, which corresponds to an optical-to-optical conversion of efficiency of 2.17 % [6].…”
Section: Introductionmentioning
confidence: 99%
“…It's important to produce compact and high quality (high-efficiency and widely-tunable) MIR laser. A number of mid-infrared continuous waves based on IC-OPO have been reported [6][7][8][9][10][11][12]: Carleton et al reported a CW IC-OPO based on PPRbTiOAsO4 pumped by 1064nm Nd:YVO4 laser. At 3 W of input diode-laser, the maximum power of 65 mW of idler at 3.52 μm was obtained, which corresponds to an optical-to-optical conversion of efficiency of 2.17 % [6].…”
Section: Introductionmentioning
confidence: 99%
“…Periodically poled lithium niobate (PPLN) is an ideal and the most comprehensive crystal for the OPO process. In 2003, Abitan and Buchhave reported an intracavity CW SR-OPO based on periodically poled lithium niobate (PPLN) as the nonlinear medium [26]. In 2004, a tunable intracavity CW PPLN SR-OPO pumped by diode-pumped ring-cavity Nd:YAG laser was demonstrated and the idler tunable range was from 2.3 to 3.9 m [27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the use of intra-cavity SROs have been proved to be an efficient and low-cost technique to generate cw mid-infrared lasers [11][12][13][14][15]. In 1997, the first cw intra-cavity SRO was reported by Colville [11].…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of quasi-phase-matching (QPM) materials, QPM technology is developed rapidly. In 2003, an intra-cavity cw SRO based on periodically poled lithium niobate (PPLN) as the nonlinear gain medium was reported [13]. The SRO was placed inside the cavity of a diode-end-pumped Nd:YVO 4 ring laser.…”
Section: Introductionmentioning
confidence: 99%